Combating the Crime of Abortion and Midwife Selling Baby in Criminology Perspective - Yopiza Yopiza; Poppy Fristy (IHSA Institute, 2022)
Abortion or known as abortion provocatus is not only a medical or health problem, but also a problem that arises because humans follow Western civilization. According to Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons Article 1 paragraph (1), trafficking in persons is the act of recruiting, transporting, harboring, sending, transferring or receiving someone with threats of violence, use of force, kidnapping, confinement, forgery, fraud, abuse of power or position of vulnerability, debt bondage or giving payments or benefits, so as to obtain the consent of a person having control over another person, whether carried out within a country or between countries, for the purpose of exploitation or causing people to be exploited. The act of provocatus abortion is not allowed in the articles of the Criminal Code, even provocatus abortion is prohibited by rape victims for women, so it is clear that these articles (Article 341 and Article 342 of the Criminal Code) constitute abortion provocatus killing the child in the fetus. Efforts that can be made in providing legal protection to children as victims of criminal acts of trafficking in persons on the principle of legality have been regulated in the 1945 Constitution of the Republic of Indonesia and national legal regulations in the form of laws and Presidential Regulations as well as TAP MPR and are also regulated in the provisions of international law which have been adapted into Indonesian positive law. Efforts that can be made to ensure legal protection for children as victims of the crime of trafficking in persons are reflected in 3 stages, namely (a) at the time of the occurrence of the crime of trafficking in persons, (b) the stage of trial for the perpetrator of the crime of trafficking in persons (c) the stage after the court's decision on perpetrators of the criminal act of trafficking in persons concluded from the provisions of Law no. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons and Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.